2022
DOI: 10.1038/s41598-022-11068-0
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infections in infants

Abstract: The study aimed to analyse the clinical course of COVID-19 in 300 infants, selected from 1283 children diagnosed with COVID-19 between March and December 2020, registered in the SARSTerPED multicenter database. Most of the infants were registered in October and November 2020. 44% of the group were girls, and 56% were boys. At diagnosis, the most common symptoms were fever in 77% of the children, cough in 40%, catarrh in 37%. Pneumonia associated with COVID-19 was diagnosed in 23% of the children, and gastroint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 49 publications
6
14
0
1
Order By: Relevance
“…Co-morbidities, including birth defects, epilepsy, prematurity, atopic dermatitis, bronchopulmonary dysplasia, and immunodeficiency, were reported in 12% of the hospitalized infants. According to the authors, the actual incidence of COVID-19 in children is underestimated due to the lack of diagnoses of mild and asymptomatic courses [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-morbidities, including birth defects, epilepsy, prematurity, atopic dermatitis, bronchopulmonary dysplasia, and immunodeficiency, were reported in 12% of the hospitalized infants. According to the authors, the actual incidence of COVID-19 in children is underestimated due to the lack of diagnoses of mild and asymptomatic courses [11].…”
Section: Discussionmentioning
confidence: 99%
“…Patients also report diarrhea, abdominal pain, vomiting, fatigue, headache, loss of smell and taste, muscle aches, and shortness of breath [9,10]. About 15% of infected children develop severe COVID-19 with pneumonia, while 5% of patients develop thrombosis, septic shock, and multiorgan failure due to a cytokine storm resulting from an abnormal immune system response [11]. The group of children at risk of severe COVID-19 is made up of newborns, children with obesity, and coexisting chronic diseases (such as congenital diseases of the heart, lungs, and respiratory tract, malnutrition, and cancer) [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…While evidence suggested milder or even asymptomatic SARS-CoV-2 infections in children and adolescents (0–19 years of age; referred to hereafter as “children”) pre-Omicron, 6 , 7 , 8 more adverse health outcomes from COVID-19, including pneumonia, thrombosis, septic shock, MIS-C, and multiorgan failure, were documented then. 9 , 10 , 11 , 12 , 13 , 14 The lower risk of disease in children “pre-Omicron”, combined with concerns about vaccine safety and parental hesitancy, led to limited vaccine uptake and slow implementation of vaccination in children globally (particularly for children of <12 years of age). 15 , 16 Vaccines for children were also largely inaccessible in many parts of the world that were lagging behind in the vaccination of adults, particularly in low and middle-income countries (LMICs).…”
Section: Introductionmentioning
confidence: 99%
“…A recent report from Poland showed that during the second COVID-19 wave, 30% of affected children were infants, which increased from 10% during the first wave. Around 98% of the infants had mild disease, and none had severe disease [ 15 ]. A nationwide American study reported outcomes for under-5 children affected by the Omicron variant compared to those infected by the Delta variant.…”
Section: Epidemiology Of Covid-19mentioning
confidence: 99%
“…In contrast to adult data, epidemiologic studies in neonates and children have shown that over 90% of those affected have asymptomatic or mild disease [ 8 , 9 , 10 ]. Despite a recent surge in pediatric and neonatal cases reported, relevant outcomes such as mortality, need for respiratory support, and hospitalization rates have remained lower compared to adults [ 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%